Green Synthesis, Physicochemical and Polarity Studies of Some Novel Biologically Active Donor Acceptor Chromophores - A. Khan, Salman; M. Asiri, Abdullah; A. El-Daly, Samy; M. Marwani, Hadi; A. Alamry, Khalid (Asian Journal of Chemistry, 2014)
Chalcones were synthesized by the reaction of acetyl ferrocene and corresponding aldehhyde under microwave irradiation. Results obtained from spectroscopic (FT-IR, 1H NMR, 13C NMR, EI-MS) and elemental analysis of synthesized compounds was in agreement with their chemical structures. UV-visible and fluorescence spectroscopy measurements provided that compound 1 and 2 are good absorbent and fluorescent. Fluorescence polarity study demonstrated that these compounds were sensitive to the polarity of the microenvironment provided by different solvents. In addition, spectroscopic and physicochemical parameters, including electronic absorption, extenction coefficient, Stokes shift, oscillator strength and transition dipole moment, were investigated in order to explore the analytical potential of synthesized compounds. The antibacterial activity of the compound 1 and 2 were first studied in vitro by the disk diffusion assay against two Gram-positive and two Gram-negative bacteria. The minimum inhibitory concentration was then determined with the reference of standard drug chloramphenicol.